2018
DOI: 10.1590/s0102-8529.2018400300003
|View full text |Cite
|
Sign up to set email alerts
|

De-securitising ‘the South in the North’? Gendered Narratives on the Refugee Flows in the European Mediascape

Abstract: This article focuses on media representations of ‘the South in the North’ crosscutting the European mediascape in 2015 and the beginning of 2016. Assuming that both identities and perceptions of in/security are socially constructed, particularly by means of discourse, that security is gendered and gender constructions are in turn built on dynamics of in/security, and that gendered power relations and representations are always entangled with other structures of inequality and domination such as racism, this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Differences in children and adolescents' representation in the media were also recognised, with an agreement about journalist reporting on younger children as being more likely to generate solidarity. Through an analysis of the gendered tropes in journalist coverage of migration on the British newspapers The Guardian and The Telegraph, Santos et al (2018) found that media coverage of migrants appeared to refer to 'young men' as to anyone between the age of 16 and 50. The representation offered of this group was that of illegitimate/ non-genuine refugees, and of economic migrants who are taking advantage of the 'refugee crisis' to reach Europe in the hope of gaining benefits and protection.…”
Section: The Commonalities Between Refugee Children and Italian Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in children and adolescents' representation in the media were also recognised, with an agreement about journalist reporting on younger children as being more likely to generate solidarity. Through an analysis of the gendered tropes in journalist coverage of migration on the British newspapers The Guardian and The Telegraph, Santos et al (2018) found that media coverage of migrants appeared to refer to 'young men' as to anyone between the age of 16 and 50. The representation offered of this group was that of illegitimate/ non-genuine refugees, and of economic migrants who are taking advantage of the 'refugee crisis' to reach Europe in the hope of gaining benefits and protection.…”
Section: The Commonalities Between Refugee Children and Italian Childrenmentioning
confidence: 99%
“…Usually, young men, and particularly those identified with a certain racial or cultural group or with the Global South, are frequently represented in the media and in policy and political discourses as inherently problematic, associated with negative perceptions and threats to urban, national and international security. (Santos et al, 2018, p. 457)…”
Section: Key Informant Review Of the Italian Media Representation Of ...mentioning
confidence: 99%
“…The 'nation at war' narrative enables them to rationalize antisocial attitudes and harsher treatment of immigrants and minorities. Depictions of people on the move as threatening articulate the securitization of migration; that is, moving human mobility from the category of normal political phenomena to that of security (Santos et al, 2018).…”
Section: Anti-immigration and Femonationalismmentioning
confidence: 99%